Production of molecular hydrogen formed by the thermal and radiation-thermal transformation of water in the nano-Si+H₂O system - Jafarov, J.D.; Bashirova, S.M.; Eyubov, K.T.; Garibov, A.A. (Вопросы атомной науки и техники, 2019)
It were studied the regularities of the dependence of the yield of molecular hydrogen obtained during the thermal and radiation-thermal transformation of water under the action of gamma quanta (⁶⁰Co, P = 18.17 rad/s) on the nano-Si+H₂O system with particle sizes dSi = 50 nm on the temperature (T = 300, 373, 473, 573, 623, and 673 K) of the total system and on the water vapor density (p = 0.25, 0.5, 1, 3, and 8 mg/cm³) at a constant temperature of T = 673K. In this system, in a reaction medium with a water vapor density p=8 mg/cm³ in the temperature range 300 ≤ T ≤473 K, molecular hydrogen is obtained only by radiation-thermal, and in the temperature range 573 ≤ T ≤ 673 K – by thermal and radiation-thermal methods. In the temperature range 300 ≤ T ≤ 473 K, the activation energy of the radiation-thermal process is 1.07 kJ/mol, and in the temperature range 573 ≤ T ≤ 673 K, the activation energy of the thermal and radiation-thermal processes is 68.6 and 53.83 kJ/mol, respectively. At a temperature of T = 673 K, the yield and the rate of formation of molecular hydrogen obtained in the thermal and radiation-thermal transformation of water vapor in the reaction medium increase in direct proportion to the its density at ρ < 3 mg/cm³, and at ρ ≥ 3 mg/cm³ a sharp decrease in the angle slope is observed. Досліджено закономірності залежності виходу молекулярного водню, отриманого при термічному і радіаційно-термічному перетворенні води під впливом гамма-квантів (⁶⁰Co, P = 18,17 рад/с) на систему нано-Si+Н₂О з розмірами частинок dSi = 50 нм, від температури (T = 300, 373, 473, 573, 623 і 673 K) загальної системи, а також від щільності парів води (p = 0,25; 0,5; 1; 3 і 8 мг/см³) при постійному значенні температури T = 673 K. У цій системі в реакційному середовищі з щільністю парів води p = 8 мг/см³ і в інтервалі температур 300 ≤ T ≤ 473 K молекулярний водень виходить тільки радіаційно-термічним, а в інтервалі 573 ≤ T ≤ 673 K – термічним і радіаційно-термічним способами. При 300 ≤ T ≤ 473 K енергія активації радіаційно-термічного процесу становить 1,07 кДж/моль, а при 573 ≤ T ≤ 673 K енергії активації термічного і радіаційно-термічного процесів – 68,6 і 53,83 кДж/моль. При T = 673 K вихід і швидкість утворення молекулярного водню, отриманого при термічному і радіаційно-термічному перетворенні парів води в реакційному середовищі, ростуть прямо пропорційно їх щільності (ρ < 3 мг/см³), а при значеннях ρ ≥ 3 мг/см³ спостерігається різке зменшення швидкості утворення молекулярного водню. Исследованы закономерности зависимости выхода молекулярного водорода, полученного при термическом и радиационно-термическом превращении воды под воздействием гамма-квантов (⁶⁰Co, P = 18,17 рад/с) на систему нано-Si+Н₂О с размерами частиц dSi = 50 нм, от температуры (T = 300, 373, 473, 573, 623 и 673 K) общей системы, а также от плотности пара воды (p = 0,25; 0,5; 1; 3 и 8 мг/см³) при постоянном значении температуры T = 673 K. В этой системе в реакционной среде с плотностью паров воды p = 8 мг/см³ и в интервале температур 300 ≤ T ≤ 473 K молекулярный водород получается только радиационно-термическим, а в интервале температур 573 ≤ T ≤ 673 K - термическим и радиационнотермическим способами. При 300 ≤ T ≤ 473 K энергия активации радиационно-термического процесса составляет 1,07 кДж/моль, а при 573 ≤ T ≤ 673 K энергии активации термического и радиационнотермического процессов соответственно – 68,6 и 53,83 кДж/моль. При T = 673 K выход и скорость образования молекулярного водорода, полученного при термическом и радиационно-термическом превращении паров воды в реакционной среде, растут прямо пропорционально их плотности (ρ < 3 мг/см³), а при значениях ρ ≥ 3 мг/см³ наблюдается резкое уменьшение скорости образования молекулярного водорода.